Rape Culture and the Bible: Scholars Reflect - Thiede, Barbara (Rape Culture, Religion and the Bible, 2025)
Rape Culture and the Bible: Scholars Reflect offers readers the opportunity to hear from prominent and influential biblical scholars and scholar activists as they reflect on their work on sexual violence vis-a-vis the Bible. This book covers major points of inquiry in the field, focusing primarily on the Hebrew Bible and the New Testament. It explores debates on appropriate terminology; intersectionality of sexual violence, gender, and race; how survivor perspectives inform the reading of violent texts; male-on-male sexualized violence in biblical literature; and the connections of Judeophobia with sexual violence in early Christian literature. The introductory chapter establishes methodology, purpose, and aims of this volume. The final chapter reflects on the ethical concerns governing the field, challenges scholars have faced in their discipline, and the tasks ahead. Along the way, Rape Culture and the Bible demonstrates how rape and rape culture in the Bible impact real lives across time and the globe. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license